Serving both rich and poor - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Jin Jokwi Simon, the provincial chief for water and sanitation in North West Cameroon, explaining that irrigated agriculture may soon raise the issue of water rights in the province.